1994
DOI: 10.1172/jci117539
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation-dependent changes in release of arachidonic acid from endothelial cells.

Abstract: Stimulation of endothelial cells resulted in release of arachidonic acid from phospholipids. The magnitude of this response decreased as the cells became confluent and the change coincided with a decrease in the percentage of cells in growth phases (G2 + M); this was not a consequence of time in culture or a factor in the growth medium. Preconfluent cells released 30% of arachidonic acid; confluent cells released only 6%. The decreasing release of arachidonic acid was demonstrated using metabolic labeling, mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 61 publications
5
31
1
1
Order By: Relevance
“…7). This represents a novel molecular switch for the control of endothelial prostaglandin generation and accounts for earlier observations that confluent endothelial cells generate lower levels of prostaglandins compared with nonconfluent endothelial cells (14,15). In this study, we describe the Ca 2ϩ -induced association of cPLA 2 ␣ with the ER/ERGIC of nonconfluent HUVECs.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…7). This represents a novel molecular switch for the control of endothelial prostaglandin generation and accounts for earlier observations that confluent endothelial cells generate lower levels of prostaglandins compared with nonconfluent endothelial cells (14,15). In this study, we describe the Ca 2ϩ -induced association of cPLA 2 ␣ with the ER/ERGIC of nonconfluent HUVECs.…”
Section: Discussionmentioning
confidence: 60%
“…2ϩ Elevation Targets cPLA 2 ␣ to Intracellular Membranes in Subconfluent Endothelial Cells-cPLA 2 ␣ activity is greater in subconfluent endothelial cells than in quiescent, confluent endothelial cells (15,16). We have previously shown that subconfluent and confluent endothelial cells (see supplemental Fig.…”
Section: Cytosolic Camentioning
confidence: 89%
See 2 more Smart Citations
“…It is possible that entry into the nucleus simply provides cPLA 2-α with an additional pool of phospholipid substrate. Previous data have shown that actively growing endothelial cells are able to liberate more arachidonic acid than growth-arrested cells (Whatley et al, 1994). Thus, while endothelial cells are proliferating, for example at sites of wounds, they can produce elevated levels of prostacyclin, resulting in decreased platelet activation.…”
Section: Future Perspectivesmentioning
confidence: 99%